Digital media ethics - Ess, Charles (Digital media and society series, 2014)
The original edition of this accessible and interdisciplinary textbook was the first to consider the ethical issues of digital media from a global perspective, introducing ethical theories from multiple cultures. This second edition has been thoroughly updated to cover current research and scholarship, and recent developments and technological changes. It also benefits from extensively updated case-studies and pedagogical material, including examples of watershed events such as privacy policy developments on Facebook and Google+ in relation to ongoing changes in privacy law in the US, the EU, and Asia. New for the second edition is a section on citizen journalism and its implications for traditional journalistic ethics. With a significantly updated section on the ethical toolkit, this book also introduces students to prevailing ethical theories and illustrates how they are applied to central issues such as privacy, copyright, pornography and violence, and the ethics of cross-cultural communication online.